Changes in the intestinal microbiota in preterm infants in a tertiary hospital in Peru - Flores de Valgas-Velez, Lissette (2022)
Background: The Intestinal Microbiota (IM) of the preterm newborn (RNP) is modified by factors such as hospitalization, antibiotics, postnatal nutrition, among others. The study: Observational - longitudinal research with the objective of analyzing the changes in MI promoted by the type of breastfeeding received in neonates <37 weeks of gestational age. Samples of 23 neonates hospitalized in the Intensive Care Units (NICU) and Neonatology were analyzed. Findings: No significant difference was found in the development of IM with respect to the type of feeding, however a different trend was observed among the neonates fed with Human Milk (HL) that increased the amount of Lactococcus and Clostridium while they decreased Lactobacillus, opposite to the group fed with Mixed Lactation (BF) that increased the abundance of Lactobacillus and decreased Lactococcus and Clostridium; Conclusion: It is concluded that the specific members of the MI of the RNP depend on the dynamic interaction between the host and the type of dietary selection.